Comparação da força isocinética entre nadadores de técnicas de nado alternadas e simultâneas - Souza, Brian Charlesson da Silva (Brasil, 2022)
Swimming is a sport that demands the continuous use of the upper limbs, and this involves the recurrent use of the shoulder joint, which can cause pain and, consequently, injures. The objective of this study is to verify if there are differences in isokinetic strength variables in swimmers with alternating and simultaneous swimming techniques. Thirty-eight swimmers were evaluated and divided into two groups according to their respective swimming techniques: Group 1 Alternate (N=19); Group 2 Concurrent (N=19). The strength level of the shoulder rotators, flexors and extensors was assessed with an isokinetic dynamometer on only one occasion using two protocols: 3 repetitions at 60°/s and 20 repetitions at 180°/s. There were differences in the variables: Flexion variation coefficient at 180°/s (U = 110.500; p < 0.05) and conventional flexor/extensor balance ratio at 60°/s (U = 112.000; p < 0.05) for the group of alternating swimming techniques and conventional flexor/extensor Equilibrium Ratio at 60°/s [U = 8.223; p < 0.05] for the group of simultaneous swimming techniques. This suggests that there are few relationships between isokinetic variables when compared with different swimming techniques.